Laxative Activity of Trigonella Foenum-Graecum Fenugreek Seeds on Loperamide Induced Constipation in Rats (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: Fenugreek Seeds; Laxative activity; Constipa- tion; Trigonella foenum-graecum